Functional variants in the promoter region of sulfotransferase 1C1 gene associated with estrogen degradation in gilts. (4th June 2022) - Gao, Qinxue; Chu, Qingpo; Liu, Mingzheng; Gao, Siyuan; Xu, Qinglei; Zhou, Bo
Abstract: Chinese indigenous Mi gilts have clearer estrus expression than European Large White gilts, and sulfotransferase 1C1 ( SULT1C1) gene was differentially expressed between them. To investigate the differential expression mechanism of porcine SULT1C1 gene, we cloned its promoter region and predicted its activity. Six deletion expression vectors (P1, P2, P3, P4, P5, and P6) for the promoter of SULT1C1 gene were constructed. Vector P3 (−1084/+261) had the highest expression activity, whereas vector P4 (−642/+261) showed a reduced in promoter activity, which suggests that the core promoter region of SULT1C1 gene is located between −1084 bp and −642 bp. Two single nucleotide polymorphisms (SNPs), c. – 994 G > A (rs345070974) and c. – 946 G > A (rs337902009) were found in Mi and Large White gilts between −1100 and −661 bp, and the expression vectors with four haplotypes (GG, AA, GA, and AG) of two SNPs were constructed. The relative luciferase activity of vector with haplotype GG was the greatest among four vectors. These indicate that c. – 994 G > A and c. – 946 G > A are key mutations for promoter activity of SULT1C1 gene. Porcine SULT1C1 promoter with −994 G allele and −946 G allele significantly improved the gene expression level. It could be involved in different estrus expression between Large White and Mi gilts.